1999
DOI: 10.1111/j.1600-0714.1999.tb02004.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin (OPN) distribution in premalignant and malignant lesions of oral epithelium and expression in cell lines derived from squamous cell carcinoma of the oral cavity

Abstract: The objectives of this study were to assess the immunolocalization of human osteopontin (OPN) in oral lesions and to identify human cell lines of oral squamous cell carcinoma (OSCC) origin that express OPN mRNA. OPN was localized using immunohistochemistry in the following oral specimens: normal epithelium (n=6), epithelial hyperplasia (n=4), epithelial dysplasia (n=28), carcinoma in situ (n=11) and squamous cell carcinoma (n=43). Cell lines UMSCC‐1, MDA TU 138, MDA 686LN, SCC4, SCC9, SCC25, CAL 27 and MDA 148… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 21 publications
6
41
0
2
Order By: Relevance
“…In OSCC samples (group II A), 95% of cytoplasmic & membrane immunoreactivity was observed in the tumour islands [Table/ Fig-1a-d]. These results were in accordance with the findings of Devoll et al, who reported significant percentage of OPN expression in cell lines derived from OSCC [18]. However, one case of OSCC in our study showed negative immunoreactivity for OPN.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…In OSCC samples (group II A), 95% of cytoplasmic & membrane immunoreactivity was observed in the tumour islands [Table/ Fig-1a-d]. These results were in accordance with the findings of Devoll et al, who reported significant percentage of OPN expression in cell lines derived from OSCC [18]. However, one case of OSCC in our study showed negative immunoreactivity for OPN.…”
Section: Methodssupporting
confidence: 92%
“…There was a negative expression of OPN in all the 20 samples of normal oral mucosa [Table/ Fig-3a&b]. A similar expression was also seen in the studies conducted by Devoll et al, & Zhou et al, [18,19]. In OSCC samples (group II A), 95% of cytoplasmic & membrane immunoreactivity was observed in the tumour islands [Table/ Fig-1a-d].…”
Section: Methodssupporting
confidence: 67%
“…OPN is usually absent or expressed at a low level in normal tissues but is up-regulated in certain preneoplastic and neoplastic epithelia (63)(64)(65), including that of the breast (6). Indeed, OPN overexpression has adverse prognostic significance in human breast cancer (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, osteopontin-null or osteopontin-deficient mice (11,12) show no developmental abnormalities or gross bone deformities unless intervention studies are done, suggesting protein redundancy for normal development and differentiation and that overexpression of osteopontin is more important in pathologic conditions, such as tumor development. Elevated expression of osteopontin has been reported in benign (13)(14)(15) and malignant tumors from organs, such as brain, breast, mouth, salivary glands, thyroid gland, lung, stomach, endometrium, ovary, kidney, colon, prostate, liver, and pancreas (10,16,17). Furthermore, elevated levels of osteopontin were detected in serum from breast, ovary, colon, prostate, pancreas, and lung cancer patients (10,17).…”
Section: Introductionmentioning
confidence: 99%